Modification of structural and physicochemical properties of repeated freeze-thawed cycle maize starch. Issue 1 (1st January 2020) - Liu, Yu; Gao, Jinmei; Feng, Duo; Zhao, Jiangyan; Guo, Yu; Zhao, Jian; Li, Wenhao; Yan, Wenjie
ABSTRACT: To investigate the effects and mechanisms of repeated freeze-thaw cycles treatment on starch-based foods, structural and physicochemical properties of maize starch granules were investigated under repeated freeze-thaw treatment with 0, 3, 6, 12, 18 and 24 times at −20 °C, −40 °C and −80 °C, respectively. The x-ray crystalline pattern of the maize starch was A-type after freeze-thawing process. Meanwhile, the peak, though, final and setback viscosity, pasting temperature, water holding capacity, transparency and hydrolysis rate of samples significantly ( P < .05) increased, while the breakdown decreased with the increase of freeze-thaw numbers. However, the increased freezing temperatures from −80 °C to −20 °C had non-significantly effects on the structure with the approximate phenomenal and the physicochemical properties like thermal properties, setback, hydrolysis rate, water holding capacity, transparency and syneresis under a same freeze-thaw cycle time. Graphical abstract: